Analisis Peluang, Tantangan, dan Strategi Industri Halal di Indonesia - Rina Samsiyah; Luluwatun Nazla; Silva Nur'aini; Frida Aprilya Saqina; Lina Marlina (CV. Doki Course and Training, 2025)
Indonesia as a country with the largest Muslim population in the world, has great potential in the halal industry. The term